O lúdico como recurso didático para o ensino aprendizagem da criança com síndrome de Down - PEREIRA, Elza do Socorro Ferreira (2024)
The present work has as its theme “The ludic as a didactic resource for the teaching-learning of the child with Down Syndrome”. This work has as objective analyze the importance of play as a didactic resource in the teaching-learning process of students with Down Syndrome from Associação de Pais e Amigos of the Exceptional (APAE) and the Dr. Vicente Maues. And as specifics: Check how the ludic contributes to the development of Teaching-Learning of the handicapped with Down Syndrome; Knowing how teachers APAE and Escola Dr. Vicente Maués, afternoon shift, can use the ludic to to develop the motor coordination of students with Down Syndrome; and, realize what is the teacher's relationship with the Down Syndrome student in the APAE entity and in the School Dr. Vicente Maues. Seeking to answer these questions, we chose for carrying out a research with an inductive method, with a qualitative approach with application of questionnaires and observations in the aforementioned Educational Institutions. At the end of the research, we conclude that the ludic becomes necessary for the learning of students with Down Syndrome.